Co-occurrence of Autism, Psychosis and Catatonia : A Scoping Review - Nyrenius, Johan ; 0000-0002-1816-6098; Zander, Eric ; 0000-0002-2267-5813; Ghaziuddin, Mohammad; Ghaziuddin, Neera (Journal of Autism and Developmental Disorders, 2025)
Purpose: Autism, psychosis and catatonia were once considered part of schizophrenia. While both autism and catatonia have been “detached” from schizophrenia, co-occurrence of the three conditions may be suspected in some cases, because of overlapping features, leading to challenges in diagnosis and treatment. This review provides an overview of the literature regarding the co-occurrence of autism, psychosis and catatonia. Methods: A scoping review of peer-reviewed original research articles that simultaneously described all the three diagnostic constructs (autism, psychosis and catatonia) was performed. Using PRISMA-ScR guidelines, the review was based on MedLine, Scopus, PsycInfo and Cinahl databases. Studies included patients of all ages, races and both genders. A Qualitative Content Analysis (QCA) of the contents of the articles was also performed. Results: Seventeen articles (n = 17) out of a total of 752 (after removing duplicates) met inclusion criteria, most of which (65%) were case reports/case series. Overall, majority of the studies lacked description of diagnostic procedures regarding psychosis - especially while describing co-occurrence of psychosis and catatonia in patients with autism. Reports of treatment outcomes showed considerable variations. Major themes identified in the QCA involved uncertainty, particularly in the differential diagnostic and treatment considerations. Conclusion: The results of this scoping review underscore a need for undertaking larger studies using structured diagnostic approaches for developing better methods to differentiate between autism, psychosis and catatonia. Our findings also point to a need for conducting treatment trials and developing treatment algorithms for mixed presentations when there is co-occurrence of autism, psychosis and catatonia.
Publisher Copyright: © The Author(s) 2025.
Keywords: Catatonia - autism spectrum disorder; Co-occurrence; Neurodevelopmental disorders; Psychosis